A new species of genus Nirvana (Hemiptera: Cicadellidae: Evacanthinae) with note on female genitalia from India - Meshram, Naresh M.; Rai, Stuti (Zootaxa, 2017)
The leafhopper genus Nirvana Kirkaldy (Hemiptera: Cicadellidae: Evacanthinae) is reviewed, and to the 6 species known so far, one new species Nirvana subsuturalis is added and described from Indian subcontinent. Habitus photographic illustrations, with note on female genitalia, key for all species from the Indian subcontinent is provided.